2014
DOI: 10.3233/jad-131457
|View full text |Cite
|
Sign up to set email alerts
|

Isorhynchophylline Treatment Improves the Amyloid-β-Induced Cognitive Impairment in Rats via Inhibition of Neuronal Apoptosis and Tau Protein Hyperphosphorylation

Abstract: The progressive accumulation of amyloid-β (Aβ) in the form of senile plaques has been recognized as a key causative factor leading to the cognitive deficits seen in Alzheimer's disease (AD). Recent evidence indicates that Aβ induces neurotoxicity in the primary neuronal cultures as well as in the brain. Previously, we have demonstrated that isorhynchophylline (IRN), the major chemical ingredient of Uncaria rhynchophylla, possessed potent neuroprotective effects. In the present study, we aimed to investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 53 publications
0
43
0
Order By: Relevance
“…Reducing the amount of beta-amyloid protein (Aβ) and tau protein in the brain and modulating Aβ toxicity, including inflammatory response, oxidative stress, and neuronal apoptosis, have been considered the most promising therapeutic strategies available for controlling the progression of dementia [23, 24]. …”
Section: Discussionmentioning
confidence: 99%
“…Reducing the amount of beta-amyloid protein (Aβ) and tau protein in the brain and modulating Aβ toxicity, including inflammatory response, oxidative stress, and neuronal apoptosis, have been considered the most promising therapeutic strategies available for controlling the progression of dementia [23, 24]. …”
Section: Discussionmentioning
confidence: 99%
“…Among Uncaria species, U. tomentosa was considered as effective antitumor candidate to inhibit cancer cells growth, such as HL-60 (leukemia) (Cheng et al, 2007;Bacher et al, 2006), MCF7 and MT-3 (breast) (Riva et al, 2001;Sun et al, 2012a;Pilarski et al, 2010;García Giménez et al, 2010), (Dreifuss et al, 2013) 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 Xian et al, 2014Xian et al, et al, 2007. The correlations between pharmacological properties of U. tomentosa and active compounds revealed that oxindole alkaloids and triterpenes are major bioactive constituents.…”
Section: Anticancer Activitiesmentioning
confidence: 98%
“…The doses of the honokiol were selected with reference to previous studies (Qu et al, 2012;Vavilala et al, 2013). Donepezil hydrochloride was used as the positive control (Xian et al, 2014). Honokiol was dissolved in sterile saline containing 10% dimethyl sulfoxide (DMSO), while SCOP and donepezil were dissolved in normal sterile saline.…”
Section: Drug Treatmentmentioning
confidence: 99%
“…The Morris water maze test was conducted as described in our previous publication (Xian et al, 2014), with minor modifications. The experimental apparatus (Water Mazes, TSE systems, Germany) consisted of a blank circular water tank (100 cm in diameter, 35 cm in height), containing water (23 71 1C) to a depth of 15.5 cm, which was rendered opaque by adding ink.…”
Section: Morris Water Maze Testmentioning
confidence: 99%